The Influence of Religiosity and Social Environment on The Intention To Save Darussalam Gontor University Lecturers in Sharia Bank - Lahuri, Setiawan bin; Adillah, Erika Rishan; Zuhroh, Ainun Amalia (IAIN Kudus, 2023)
This article aims to find out how much influence the religiosity and social environment of Darussalam Gontor University lecturers have on saving in sharia banks. Gontor University lecturers are lecturers who live in an Islamic boarding school environment. This research is research with a quantitative analysis approach. Primary research data is based on a sample of 82 respondents taken using purposive sampling. The analysis uses data quality tests, classical assumption tests, multiple linear analysis tests, and statistical tests using the Statistical Product and Service Solution analysis tool version 22. The results of the research show that the religious variable has a significant positive effect on the intention to save at the bank. This is because the majority of respondents have a high level of religiosity, and respondents pay more attention to the use of services and products in implementing Islamic law. Social and environmental variables have no effect on interest in saving at Islamic banks. This is because respondents use more religiosity factors in saving behavior. Then simultaneously, the religiosity and social environment variables influence the intention to save at a sharia bank by 52.4%, and 47.6% are influenced by other variables. This research recommends that Islamic banks pay more attention to sharia systems and principles